Teaching Learning: A Study of Strategies Adopted in Government Elementary Schools - Jadeja, Kripali (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
Sarva Shiksha Abhiyaan (SSA) has been one of the breakthroughs in terms of innovative strategies adopted to ensure free and compulsory education for all after year 2000 to attract children into the school. Many other initiatives merged under the bigger project of SSA. As a result gross enrollment rate in the year 2000-01 was 81.6 per cent which increased to 96.9 per cent in the year 2015-16 (MHRD, 2018) which show that students entered in the school. Now, it becomes pertinent so look at the school related aspects which would play important part in children’s successful completion of elementary education where teaching learning becomes critical to focus on.